Análise de observação do ensino de Libras como L1 e L2 - Corrêa, Rhana Letícia Thomé (Brasil, 2023)
This work presents the Final Report of Internship in Teaching Libras as L1 and L2 in the Letters-Libras course at the Federal University of Amazonas. It was based for the teaching of Libras in L1 in the following authors QUADROS (2000), LEITE (2004), FIORIN (2013), ALBRES E SARUTA (2012), PIMENTA and LIMA (2004) and for the teaching of Libras as L2 in the authors GESSER(2010), Leite(2004), WILCOX & WILCOX(1991a 1991b) translated by LEITE(2005) and SÁ (2009) . The methodology used was classroom observation from July 25 to August 22, 2022 at Escola Instituto Filippo Smaldone and from August 28 to September 4, 2019 at Escola Estadual de Atendimento Específico Mayara Redman Abdel Aziz, also deaf teachers of Libras showed their practices and experiences during the disciplines and were reported in this work. After the analysis, the following conclusion was reached: the supervised internship is an essential activity in the construction of the professional identity, because it is at this moment that we will experience in practice the theories that we study during graduation and in the future how we will solve problems during our teaching. of L1 and L2 of Brazilian Sign Language.